1995
DOI: 10.1002/hc.520060111
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of bis(dialkylamino)carbeniumdithiocarboxylates

Abstract: 2-Chloro and 2-phenoxy substituted 1 ,I -bis(diethylamino)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The combined extracts were dried over MgSO 4 and evaporated. The residue was recrystallized from CH 2 Cl 2 / hexane to give 116 mg (83%) of the inner salt I as red needles, mp 98.0-98.5ЊC [3].…”
Section: Reaction Of the Carbenium Salt 4b With Na 2 Smentioning
confidence: 99%
See 1 more Smart Citation
“…The combined extracts were dried over MgSO 4 and evaporated. The residue was recrystallized from CH 2 Cl 2 / hexane to give 116 mg (83%) of the inner salt I as red needles, mp 98.0-98.5ЊC [3].…”
Section: Reaction Of the Carbenium Salt 4b With Na 2 Smentioning
confidence: 99%
“…However, information on their reactivities is still limited; 1,3-dipolar cycloaddition with alkynic dipolarophiles and S-methylation with methyl iodide are typical reactions reported on these inner salts [1]. In recent years, we have been investigating the synthesis, structure, and reactivities of the inner salt, 2,2-bis(diethylamino)-2-ethylium-1-dithioate (1), and the related compounds [2][3][4][5][6][7][8]; 1 is readily obtainable by reaction of 1-chloro-2,2-bis(diethylamino)ethene with elemental sulfur [2,3]. Quite recently, we have found that 1 reacts with negatively charged nucleophiles, such as Grignard reagents and alkyllithiums, at the negatively charged dithiocarboxylate sulfur atom to afford a range of ethenethiolates 3 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The mixture turned from colorless to purple, which was slowly warmed to room temperature and stirred for 1.5 days. The mixture was purified by silica-gel column chromatography with dichloromethane-ethyl acetate (95:5) as the eluent to give 96 mg (13%) of 1c: mp 96.0-97.5ЊC (mp 98ЊC [8] …”
Section: 2-bis(diethylamino)-2-ethylium-1-dithioate (1e)mentioning
confidence: 99%
“…Thus, peraminoethenes (2) reacted with carbon disulfide to give the corresponding salts 1 (Scheme 1) [2][3][4][5]. The other method involves sulfuration of 1,1-bis(dialkylamino)ethenes by elemental sulfur [6][7][8]. The sulfuration of 1,1-bis(dialkylamino)ethenes (3) with elemental sulfur afforded the salts 1 in about 50% yields for two examples (Scheme 2) [6], while the sulfuration of 1,1-bis(dialkylamino)-2-chloroethenes (4) with sulfur in the presence of triethylamine gave 1 in much better yields [7,8].…”
Section: 2-bis(dialkylamino)-2-ethylium-1-dithioatesmentioning
confidence: 99%
See 1 more Smart Citation